Molecular markers and their Potentials in Animal Breeding and Genetics - Salisu, I.B; Olawale, A.S; Jabbar, B; Koloko, B.L; Abdurrahaman, S.L (Nigerian Journal of Animal Science, 2023)
Over the centuries, livestock improvements largely depend on the selective breeding of the individual animals with superior phenotype. The advent of DNA markers in recent years allowed for easy selection of a number of valuable traits more directly. Molecular markers have played a significant role in animal breeding and genetics by providing the opportunities in maximizing selection particularly for those traits that have low heritability or traits for which measurement of phenotype is difficult, expensive, or only possible in late life. Different types of molecular markers such as restriction fragment length polymorphisms (RFLPs), microsatellites (SSR), and single nucleotide polymorphisms (SNPs), have been widely used in molecular breeding as they can be amplified easily through polymerase chain reaction (PCR) and could be employed to estimate the genetic diversity within or between the breeding populations. These markers can be used simply as reference points in transgenic breeding to identify the animals with specific transgenes or to select the genes/genomic regions that affect economic traits through markerassisted selection. Hence, the overall improvement in livestock species is greatly aided through the use of molecular markers.